(untitled) (Orthodontic Journal of Nepal, 2015)
Due to the distinctive orthodontic treatment methodology of the Alexander Discipline; thousands of clinicians around the world perform its 20 master principles. An outgrowth of the Tweed technique, these basic principles has been established over many years in author’s own practice. This review presents evolution of the appliance, the concept of Vari-Simplex Discipline, as well as Alexander orthodontic philosophy. This paper concisely describes finishing and retention procedures in Alexander Discipline and will be of interest to anyone involved in the study and practice of orthodontics